Filamin A mutation, a common cause for periventricular heterotopia, aneurysms and cardiac defects. Issue 4 (16th March 2009) - de Wit, M C Y; Kros, J M; Halley, D J J; de Coo, I F M; Verdijk, R; Jacobs, B C; Mancini, G M S
Abstract : Filamin A is an important gene involved in the development of the brain, heart, connective tissue and blood vessels. A case is presented illustrating the challenge in recognising patients with filamin A mutations. The patient, a 71-year-old woman, was known to have heart valve disease and bilateral periventricular nodular heterotopia when she died of a subarachnoid haemorrhage. Autopsy showed typical cerebral bilateral periventricular heterotopia and vascular abnormalities. Postmortally, the diagnosis of a filamin A mutation was confirmed. Recognition during life may prevent cardiovascular problems and provide possibilities for genetic counselling.